Effects of shoe cleat position on physiology and performance of competitive cyclists - Paton, C. (International Journal of Sports Physiology and Performance, 2009)
Purpose: Aerobic economy is an important factor that affects the performance of competitive cyclists. It has been suggested that placing the foot more anteriorly on the bicycle pedals may improve economy over the traditional foot position by improving pedaling efficiency. The current study examines the effects of changing the anterior-posterior pedal foot position on the physiology and performance of well-trained cyclists. Methods: In a crossover study, 10 competitive cyclists completed two maximal incremental and two submaximal tests in either their preferred (control) or a forward (arch) foot position. Maximum oxygen consumption and peak power output were determined from the incremental tests for both foot positions. On two further occasions, cyclists also completed a two-part 60-min submaximal test that required them to maintain a constant power output (equivalent to 60% of their incremental peak power) for 30 min, during which respiratory and blood lactate samples were taken at predetermined intervals. Thereafter, subjects completed a 30-min self-paced maximal effort time trial. Results: Relative to the control, the mean changes (±90% confidence limits) in the arch condition were as follows: maximum oxygen consumption, -0.5% (±2.0%); incremental peak power output, -0.8% (±1.3%); steady-state oxygen consumption at 60%, -2.4% (±1.1%); steady-state heart rate 60%, 0.4% (±1.7%); lactate concentration 60%, 8.7% (±14.4%); and mean time trial power, -1.5% (±2.9%). Conclusions: We conclude that there was no substantial physiological or performance advantage in this group using an arch-cleat shoe position in comparison with a cyclist`s normal preferred condition.